The Best of Both Worlds: Canada’s Normative Transcendent Purpose and Its Decision to Stop Its Airstrikes in the Syrian Civil War - Sesarianto, Kevin Ali; Rosyidin, Mohamad (Journal of International Relations, 2019)
The Syrian Civil War is yet another war in a series thereof in the Arab Spring in which the United States and its allies are involved. However, an anomaly has occurred in the military coalition: Canada has significantly decreased the degree of its involvement by stopping its airstrikes within the Western coalition’s campaign. Employing a dual-perspective of classical realism and constructivism, this thesis seeks to find the determining factors to the event using the concepts of transcendent purpose and of norm dynamics. To arrive at the conclusion, this thesis investigates norms projected by Canada in relation to its military alliances, including but not limited to NATO. This thesis finds that, on the one hand, Canada has historically always defended its image by joining military coalitions involving the United States; on the other hand, however, Canada is always reluctant to engage in wars which defy its transcendent purpose, hence the best of both worlds. This thesis concludes that Canada’s foreign policy, in line with its transcendent purpose, constitutes of two factors: the Axworthy norms and legitimacy. In the Syrian Civil War, the United States-led coalition lacks both.